Dimensional endophenotypes in Bipolar Disorder: Affective Dysregulation and Psychosis Proneness - Mahon, K (2013)
BACKGROUND: The clinical phenotype of bipolar disorder (BPD) is heterogeneous and the genetic architecture of the disorder is complex and not well understood. Given these complications, it is possible that the identification of intermediate phenotypes (“endophenotypes”) will be useful in elucidating the complex genetic mechanisms that result in the disorder. The examination of unaffected relatives is critical in determining whether a particular trait is genetically-relevant to BPD. However, few dimensional traits related to BPD have been assessed in unaffected relatives of patients. METHODS: We assessed affective temperament and schizotypy in 55 discordant sibling pairs and 113 healthy controls (HCs) using the Temperament Evaluation of Memphis, Pisa, Paris, and San Diego, Auto-questionnaire version (TEMPS-A) to assess affective temperament and the Schizotypal Personality Questionnaire (SPQ) to assess schizotypy. RESULTS: BPD patients scored significantly higher than HCs on all subscales of the SPQ and on all but one subscale (hyperthymic) of the TEMPS-A (all p <0.01). Siblings demonstrated scores that were significantly intermediate to patients and HCs on the anxious subscale of the TEMPS-A and on the interpersonal deficits and disorganized subscales of the SPQ. LIMITATIONS: We did not investigate the BPD spectrum as most patients were diagnosed with BPD I (n = 47). Most of the patients had experienced psychosis (n = 42) and so we were unable to examine whether psychosis status impacted upon affective temperament or schizotypy in patients or their siblings. CONCLUSION: These data suggest that schizotypy and affective temperament represent dimensional traits that are likely to underlie the genetic risk for BPD.